1984
DOI: 10.1093/oxfordjournals.eurheartj.a061690
|View full text |Cite
|
Sign up to set email alerts
|

Aortic input impedance in heart failure: comparison with normal subjects and its changes during vasodilator therapy*

Abstract: This study was aimed at the evaluation of aortic impedance in patients with congestive heart failure. Aortic impedance (simultaneous measurements of aortic pressure and blood flow), mean (Wm) and pulsatile (Wp) powers were compared in 11 normal subjects and in 12 patients with heart failure. Pulse wave velocity (C: modified Moëns-Korteweg equation, simultaneous measurements of aortic pressure and radius) was determined under control conditions in all normal subjects and in 7 patients with heart failure. Impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 0 publications
3
33
0
2
Order By: Relevance
“…The primary effect of reducing systemic vascular resistance appears related to its dilating effect at the arteriolar level. Other effects on aortic input impedance have suggested an effect on large artery function (23)(24)(25)(26)(27). This study documents the significant reduction in pulse wave velocity, increase in arterial compliance, and decrease in systemic vascular resistance after nitroprusside.…”
Section: Discussionsupporting
confidence: 68%
“…The primary effect of reducing systemic vascular resistance appears related to its dilating effect at the arteriolar level. Other effects on aortic input impedance have suggested an effect on large artery function (23)(24)(25)(26)(27). This study documents the significant reduction in pulse wave velocity, increase in arterial compliance, and decrease in systemic vascular resistance after nitroprusside.…”
Section: Discussionsupporting
confidence: 68%
“…Physiologic or therapeutic interventions designed to decrease the magnitude of the reflected wave or alter its timing may be beneficial in patients with heart failure. Because aortic characteristic impedance is not altered by nitroprusside, as we and others'8, 21. 24 have shown, the significant effects of nitro-720 prusside on vascular hydraulic load reside in decreases in input resistance and wave reflections.…”
Section: Discussionmentioning
confidence: 50%
“…Using pulse wave velocity as a measure of elastic behaviour, conflicting data have been observed in chronic heart failure. Arnold et al [5] reported increased pulse wave velocity and decreased brachial artery compliance, while earlier studies of Merillon et al [29] and Eliakim et al [19] could not demonstrate differences between chronic heart failure patients and controls. In addition, using characteristic impedance as a study parameter resulted in conflicting data.…”
Section: Discussionmentioning
confidence: 99%